PERBANDINGAN KETERAMPILAN PROSES SAINS SISWA ANTARA MODEL PEMBELAJARAN PROBLEM POSING DAN PROBLEM SOLVING PADA MATERI FLUIDA DINAMIS UNTUK SMA KELAS XI - Bintang Lony Vera (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study aims to determine the learning model is better between models Problem Posing and Problem Solving to improve science process skills in the subject matter of Fluid Physics High School Class XI. This study was conducted in February-April 2016 at SMAN 30 Jakarta. Sampling obtained by purposive random sampling technique which consists of two classes, namely class XI MIA 2 as an experimental class I and XI MIA 4 as an experimental class II where each class consists of 36 students. This research method is a quasi-experimental research design Nonequivalent Control Group Design. To determine the class of experiments, test the homogeneity through the value of UAS class XI SMAN 30 Jakarta MIA first. Instruments used in the form of science process skills test multiple choice reasoned. The average value of science process skills pretest the experimental class I and class II experiment in a row, namely 52.50 and 55.75 while the average daily value of science process skills in the experimental class I and class II experiment in a row is 70.50 and 75.25. The result of the calculation of the value pretest normality in both experimental class using Chi-square test showed that the data were normally distributed. The results of calculations a second class homogeneity using F-test based on data pretest showed homogeneous data, but based on the daily value data indicates the data are not homogeneous. With so to test the hypothesis using T-test data is not homogeneous. Based on the results of the daily value of science process skills drawn the conclusion that the model of problem solving can improve students' science process skills is higher than the model of Problem Posing in high school. Problem Solving so that the model is a better model used to enhance students' science process skills in physics in the classroom than the model Problem Posing. Keywords: Science Process Skills, Problem Posing, Problem Solving